A framework for failure risk-based ranking of IT projects: An AHP application - Napat Harnpornchai (2018)
© Serials Publications Pvt. Ltd. A framework for failure risk-based ranking of IT projects is proposed. While previous studies of IT project failures focus on the qualitative enumeration of the failure risk categories and failure risk factors, the present framework advances further such that the quantitative analysis and failure risk ranking is proposed. The framework applies the Analytic Hierarchy Process (AHP) as a method of ranking. The hierarchy structure of AHP is created with the risk categories, risk factors, IT project candidates at different levels of decision. By specifying the failure risk categories and failure risk factors, the ranking of IT project failure risks and thus of IT projects are accomplished via the pairwise comparison in AHP. The results from the ranking provide useful information for planning and decision making.